Prevalence and therapeutical Study of Gastrointestinal Nematodes in Local Goats in Northern of Iraq - Alaa Kamil Mahmood; Zeyad Taha Hussein; Omar-Althani S. Saed; Maher S. Owain (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this study was to study the species and prevalence GINs and detect the efficacy and resistanceof some anthelmintics in local goats in northern Iraq. A total of 180 local goats originating from 25 goatfarms were examined. As a result twelve species of these worms have been diagnosed, with a percentageof infection 64.44%, The Marshallagia spp. had the highest incidence 53.4%. The efficacy of anthelminticdrugs in the 3rd week after treatment for each the Ivermectin, A sativum, C colocynthis and O oil, reached to95.3, 62.3, 92 and 31.2% respectively, and the study noted that there is resistance to some of these therapiesby some types of worms.